'Heer Y die in thy presence': The Rewriting of Martyrs in and after Hoccleve. (19th July 2017) - Perkins, Nicholas
ABSTRACT: The Remonstrance to Sir John Oldcastle by Thomas Hoccleve ( c .1367–1426) was written in 1415 and survives in one of Hoccleve's holograph manuscripts. It was later twice copied by Richard James (bap. 1591–1638), accompanied by copious notes rereading the poem in the light of Oldcastle's then status as a proto-protestant martyr. This essay proposes that noticing James's little-studied manuscript editions and the reading and editing practices in which they are engaged can, first, enrich the reception history of Hoccleve and other late-medieval writers; and, second, prompt a re-examination of Hoccleve's own responses to the idea of martyrdom. Hoccleve's layered use of allegory and analogy between exemplary figures and readers—including his own poetic persona—draws the public anti-Lollard rhetoric of the Remonstrance into contact with personal and penitential reflections in The Regiment of Princes and the Series, and I argue that the figure of the martyr is a significant touchstone to assess the resulting blend of discourses and perspectives. Finally, I suggest that the conceptual gap between Hoccleve's and James's copies of the Remonstrance can be narrowed by recognizing that they are both recontextualizations of the poem, and their different contexts and forms effect their meanings.